2021
DOI: 10.15585/mmwr.mm7009e3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in COVID-19 Patients Requiring Mechanical Ventilation Following Implementation of a National COVID-19 Vaccination Program — Israel, December 2020–February 2021

Abstract: On February 26, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr). The availability of COVID-19 vaccines represents an opportunity to mitigate the effects of the global pandemic. Achieving high vaccination coverage through intensive vaccination campaigns has the potential to substantially reduce COVID-19-associated morbidity and mortality. Clinical trials have demonstrated the efficacy of COVID-19 vaccines in preventing mild and severe COVID-19 in a controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 2 publications
3
46
1
4
Order By: Relevance
“…Our results demonstrate that individuals who were previously infected mounted higher immune and memory responses to a single dose of vector based vaccine compared to those with no prior exposure. Earlier studies reported immune memory to SARS-CoV-2 infection ( Rodda et al, 2021 , Dan et al, 2021 ) and higher antibody response with single dose in previously infected individuals ( Rinott et al, 2021 ). Our study reports higher Memory T and B cell responses in addition to higher antibody response with single dose of COVISHIELD given at 3-6 months after recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results demonstrate that individuals who were previously infected mounted higher immune and memory responses to a single dose of vector based vaccine compared to those with no prior exposure. Earlier studies reported immune memory to SARS-CoV-2 infection ( Rodda et al, 2021 , Dan et al, 2021 ) and higher antibody response with single dose in previously infected individuals ( Rinott et al, 2021 ). Our study reports higher Memory T and B cell responses in addition to higher antibody response with single dose of COVISHIELD given at 3-6 months after recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…In the absence of specific therapeutic drugs to treat COVID-19, vaccines are currently the only alternative option in the control of SARS-CoV-2 infection ( Krammer, 2020 ). COVID-19 vaccination programs initiated worldwide resulted in decreased disease severity ( Rinott et al, 2021 ). Vaccinating huge populations need evidence based strategies for successful implementation and control of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The Covid -19 pandemic prompted scientists across the globe to design possible alternative COVID-19 vaccines 5 . Full immunization with two doses of Covid vaccine has been found to be a critical factor in preventing morbidity and mortality from the Covid-19 infection 1 . Globally the governments are trying to immunize their people as fast as possible to achieve maximum population coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study occurred prior to the deployment of COVID-19 vaccines, therefore, mortality may decrease in general as older and high-risk patients are vaccinated. 19,20,32 We acknowledge that several non-randomized studies for COVID-19 treatments (convalescent plasma, antiviral and immune-modulating agents) initially showed great potential for therapeutic bene t but failed to reveal de nitive results in randomized trials. 12,33,34 HBOT may meet with the same fate but given the effect size observed in our study, further investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%